2021
DOI: 10.5194/amt-14-6483-2021
|View full text |Cite
|
Sign up to set email alerts
|

GFIT3: a full physics retrieval algorithm for remote sensing of greenhouse gases in the presence of aerosols

Abstract: Abstract. Remote sensing of greenhouse gases (GHGs) in cities, where high GHG emissions are typically associated with heavy aerosol loading, is challenging due to retrieval uncertainties caused by the imperfect characterization of scattering by aerosols. We investigate this problem by developing GFIT3, a full physics algorithm to retrieve GHGs (CO2 and CH4) by accounting for aerosol scattering effects in polluted urban atmospheres. In particular, the algorithm includes coarse- (including sea salt and dust) and… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 7 publications
(4 citation statements)
references
References 50 publications
0
4
0
Order By: Relevance
“…Zhang et al (2015) estimated 10-20 ppm XCO 2 enhancements for CLARS-FTS measurements of the WP target by calculating the differences between CLARS-FTS Spectralon and LA TCCON measurements. Zeng et al (2021) showed typical enhancements of 20 ppm in XCO 2 and 150 ppb in XCH 4 retrieved from CLARS-FTS measurements with the GFIT3 full physics algorithm. Assuming background mole fractions of 420 ppm for CO 2 and 1900 ppb for CH 4 , these typical enhancements amount to relative variations of 5 % (CO 2 ) and 8 % (CH 4 ), and thus they are greater than our VCD b errors.…”
Section: Comparison To Clars-ftsmentioning
confidence: 93%
See 2 more Smart Citations
“…Zhang et al (2015) estimated 10-20 ppm XCO 2 enhancements for CLARS-FTS measurements of the WP target by calculating the differences between CLARS-FTS Spectralon and LA TCCON measurements. Zeng et al (2021) showed typical enhancements of 20 ppm in XCO 2 and 150 ppb in XCH 4 retrieved from CLARS-FTS measurements with the GFIT3 full physics algorithm. Assuming background mole fractions of 420 ppm for CO 2 and 1900 ppb for CH 4 , these typical enhancements amount to relative variations of 5 % (CO 2 ) and 8 % (CH 4 ), and thus they are greater than our VCD b errors.…”
Section: Comparison To Clars-ftsmentioning
confidence: 93%
“…The largest potential for improvement lies in the explicit integration of aerosol scattering in the retrieval algorithm, as shown by Zeng et al (2021). This would most likely improve fit quality, reduce uncertainty and pave the way for reliable measurement of near-ground CO 2 and CH 4 concentrations.…”
Section: Comparison To Clars-ftsmentioning
confidence: 99%
See 1 more Smart Citation
“…The Levenberg-Marquardt modification of the Gauss-Newton method is used to search the solution. The optimal estimation method has been described thoroughly in Rodgers (2000) and applied in several previous studies by the group (Zeng et al, 2017(Zeng et al, , 2021Natraj et al, 2022;Zeng et al, 2023). The parameters in the state vector to be retrieved from the algorithm are listed in Table 1.…”
Section: The Retrieval Algorithm In Fy-geoair Based On Optimal Estima...mentioning
confidence: 99%